Margaret and Margarita : Margarita Y Margaret - Reiser, Lynn (New York : Scholastic, 1993)
Margaret speaks English but not Spanish. Margarita speaks Spanish but not English. Can they still play? Of course they can! Join two girls who aren't about to let anything spoil their fun. Lynn Reiser's Margaret and Margarita/Margarita y Margaret has been used by generations of young learners. As a five-star review from a teacher put it: "I would say this book is a MUST for bilingual classrooms."